Echo-derived peak cardiac power output-to-left ventricular mass with cardiopulmonary exercise testing predicts outcome in patients with heart failure and depressed systolic function. (23rd November 2018) - Pugliese, Nicola Riccardo; Fabiani, Iacopo; Mandoli, Giulia Elena; Guarini, Giacinta; Galeotti, Gian Giacomo; Miccoli, Mario; Lombardo, Alberto; Simioniuc, Anca; Bigalli, Giovanni; Pedrinelli, Roberto; Dini, Frank L
Abstract: Aims: Peak cardiac power output-to-mass (CPOM) represents a measure of the rate at which cardiac work is delivered respect to the potential energy stored in left ventricular (LV) mass. We studied the value of CPOM and cardiopulmonary exercise test (CPET) in risk stratification of patients with heart failure (HF). Materials and results: We studied 159 patients with chronic HF (mean rest LV ejection fraction 30%) undergoing CPET and exercise stress echocardiography. CPOM was calculated as the product of a constant ( K  = 2.22 × 10 −1 ) with cardiac output (CO) and the mean blood pressure (MBP), divided by LV mass (M), and expressed in the unit of W/100 g: CPOM = [K × CO (L/min) × MBP (mmHg)]/LVM(g). Patients were followed-up for the primary endpoint, including all-cause death, ventricular assist device implantation, and heart transplantation, and the secondary endpoint that comprised hospitalization for HF. In multivariate Cox regression analyses, peak CPOM was selected as the most powerful independent predictor of both primary and secondary endpoint [hazard ratio (HR) 0.004, 95% confidence interval (CI) 0.004–0.3; P  = 0.002 and HR 0.09, 95% CI 0.02–0.55; P  = 0.009]. Sixty-month survival free from the combined endpoint was 85% in those exhibiting oxygen consumption (VO2 ) > 14 mL/min/kg and peak CPOM > 0.6 W/100 g. Peak VO2  ≤ 14 mL/min/kg provided incremental prognostic value over demographic and clinical variables, brain natriuretic peptide, and resting echocardiographic parameters (χ 2 from 58 to 64; P  = 0.04), that was further increased by peak CPOM ≤ 0.6 W/100 g (χ 2 77; P  < 0.001). Conclusion: Peak CPOM and peak VO2 showed independent and incremental prognostic values in patients with chronic HF.